Anti-cancer and anti-inflammatory new vakognavine-type alkaloid from the roots of Aconitum carmichaelii. Issue 52 (28th December 2016) - Liang, Ying; Wu, Jian-Lin; Li, Xun; Guo, Ming-Quan; Leung, Elaine Lai-Han; Zhou, Hua; Liu, Liang; Li, Na
Graphical abstract: Highlights: A new vakognavine-type alkaloid was obtained from Aconitum carmichaelii . Strong inhibitory effects on tumor cell lines with μM IC50 values. Comparable COX-2 inhibitory effect with aspirin. This represents the first report on the bioactivity of vakognavine-type diterpenoid alkaloids. Abstract: Vakognavine-type alkaloids are a rare kind of diterpenoid alkaloid isolated from Delphinium and Aconitum species. During our research on the chemical constituents of the roots of Aconitum carmichaelii, a new vakognavine-type alkaloid (1 ) along with a known vakognavine-type alkaloid, trifoliolasine E (2 ), and two known hetisine-type alkaloids (3 and4 ) were obtained. The structures were elucidated by a combination of high resolution ESI-MS, 1D and 2D NMR spectra. Compound1 showed strong inhibitory effects on HT-29, SGC-7901, and HepG2 cell lines with IC50 values of 0.948, 0.983, and 3.645 μM, respectively, while trifoliolasine E (2 ) exhibited moderate activities. Compound1 was also found to dose-dependently inhibit the activity of cyclooxygenase-2 (COX-2) with an IC50 value of 29.75 μM. To the best of our knowledge, this is the first report on the bioactivity of vakognavine-type diterpenoid alkaloids.